Contribution of Agility and Resilience to the Ability of Dribbling Football Athletes SSB Sungai Limau, Padang Pariaman Regency - Zio, Zulia Marven; Bardi, Rezafri; Syahrial, Syahrial (Yayasan Sekora, 2017)
The problem in this research is the lack of athletes' dribbling ability which makes it difficult for players to help opponents play, attract, look for opportunities to score goals so that the final goal of the game of football, which is to score as many goals against the opponent's goal, is difficult to achieve so that victory is difficult to achieve. The purpose of this study was to see the relationship between agility and dribbling ability, endurance and dribbling ability, and the role of agility and endurance to improve the dribbling ability of SSB Sungai Limau athletes. The population in this study were all SSB Limau football players in 2017 who actively participated in training (aged 16 to 17 years, 30 people). The data were analyzed using the Person's Product Moment. Based on the results of this study, it is known that there is a relationship between agility and dribbling ability (value